2009 IEEE 70th Vehicular Technology Conference Fall 2009
DOI: 10.1109/vetecf.2009.5378894
|View full text |Cite
|
Sign up to set email alerts
|

Scheduling Techniques for Improving Call Capacity for VoIP Traffic in MIMO-OFDMA Networks

Abstract: Abstract-Fourth Generation Networks will almost invariably adopt OFDMA (Orthogonal Frequency Division Multiple Access) and MIMO (Multiple Input-Multiple Output technologies, in order to meet high data rate and Quality of Service (QoS) requirements. The Worldwide Interoperability for Microwave Access (WiMAX) MAC Layer, which is based on the IEEE 802.16 standard, is designed to support a variety of applications, including voice and multimedia services. The problem of providing QoS in broadband wireless systems i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…However, for 50 users, it is observed that WFQ and PF, t c = 500, experience longer delay of 2s at the cost of facilitating fairness among users. On the contrary, the PF with t c =50K achieves lower delay of approximately 1s, whilst the Greedy scheduler achieves the lowest delay as agrees in [14] for a greedy type of scheduler serving VOIP. The trade-off of a greedy scheduler is that it sacrifices the fairness among users though it has the lowest delay from all the simulated schedulers in our scenario.…”
Section: B Multiple Sss and Downlink Scheduling Analysismentioning
confidence: 53%
“…However, for 50 users, it is observed that WFQ and PF, t c = 500, experience longer delay of 2s at the cost of facilitating fairness among users. On the contrary, the PF with t c =50K achieves lower delay of approximately 1s, whilst the Greedy scheduler achieves the lowest delay as agrees in [14] for a greedy type of scheduler serving VOIP. The trade-off of a greedy scheduler is that it sacrifices the fairness among users though it has the lowest delay from all the simulated schedulers in our scenario.…”
Section: B Multiple Sss and Downlink Scheduling Analysismentioning
confidence: 53%
“…The maximum rate scheduling is effective to advance the overall system throughput as it allocates resources to users with relatively good channel qualities among them [27]. On the other hand, the PF scheduling can improve the fairness of channel utilization among users as it distributes resources among them with consideration of their previous records of utilization [28][29][30].…”
Section: Packet Scheduling Mechanismmentioning
confidence: 99%
“…The relative strength scheduling algorithm (RSSA) proposed in [15], gives enhanced scheduling priority of weak users on their strong PRBs, resulting in a more equally distributed resource allocation process across an OFDM symbol via variation of tuning parameter.…”
Section: ) Relative Strength Scheduling Algorithm (Rssa)mentioning
confidence: 99%